MSME Empowerment Strategies through Islamic Cooperatives: A SWOT and QSPM Approach - Zainuddin Harahap; Saparuddin; Maryam Batubara (LP2M IAIN Palopo, 2026)
Purpose: This study analyzes MSME empowerment by Koperasi UMKM Syariah Sumut and identifies priority strategies consistent with Islamic economics and Maqasid al-Shariah. Methods: A descriptive qualitative case study used interviews, observation, documentation, and strategic questionnaires, supported by IFE/EFAS, SWOT/TOWS, the IE Matrix, and QSPM. Eleven informants participated. Results: The IFE score was 2.59 and EFE score 2.75. SWOT coordinates (.71; 1.13) placed the cooperative in Quadrant I, while the IE Matrix placed it in Cell V. QSPM prioritized sharia-based business mentoring (STAS 6.95), followed by digitalization (6.80), Islamic financial literacy (6.65), strategic partnerships (6.12), and halal-local product development (5.39). Implications: Financing is more empowering when integrated with continuous mentoring, institutional strengthening, digital monitoring, and Maqasid-oriented outcomes. A contextual 6P empowerment model is proposed.